TERMOGRAFIA DIGITAL POR INFRAVERMELHO DO ESCROTO E QUALIDADE DO SÊMEN EM TOUROS NELORE (BOS TAURUS INDICUS) - Felipe Rydygier de Ruediger (Colloquium Agrariae, 2014)
Aimed to study the relationship between scrotal temperature on semen quality by use of infrared thermography in Nelore bulls bred extensively. There were scrotal thermography and semen collection. Climatic data were collected by means of globe thermometer. The thermograms of the scrotum were obtained by digital infrared thermography. We carried out ejaculates through electroejaculation for analysis of quantitative and qualitative characteristics. For the data, we used analysis of variance and subsequently applied the Tukey test at 5%. (p <0.05) between animals for sperm vigor, sperm motility between animals and between crops, sperm concentration, total sperm and total viable sperm between groups, between harvests for the scrotum temperatures and climate data. It was concluded that the surface temperatures of the scrotum and climatic factors influence the quality of semen. Thermography is recommended as a complementary test in the evaluation of reproductive bulls.